Allantoin as an independent marker associated with carotid intima-media thickness in subclinical atherosclerosis - Santana,M.S. (2018)
Allantoin is the main product of uric acid oxidation and was found to be augmented in atherosclerotic plaque in human autopsy and in animal models of atherosclerosis. Uric acid is abundant in human plasma and is prone to oxidation in inflammatory conditions such as atherosclerosis. In this study, we found a significant increase in plasma uric acid (P=0.002) and allantoin (P=0.025) in participants of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) that presented common carotid intima-media thickness (c-IMT) within the 75th percentile (c-IMT≥P75). Multiple linear regression showed an association of c-IMT with uric acid (β=0.0004, P=0.014) and allantoin (β=0.018, P=0.008). This association was independent of age, the traditional risk factor LDL/HDL ratio, and non-traditional risk factors: pulse pressure, neck circumference, and the inflammatory marker myeloperoxidase. The independent and strong association of allantoin with c-IMT shows that it might be a useful marker, along with other traditional risk factors, to evaluate an early stage of atherosclerosis.